The Suran Tradition of the Village Head's Wedding in Traji: An Analysis from the Perspectives of 'Urf and Mythology in Traji Village, Parakan District, Temanggung Regency - Muhamad Hakim Nazib; Hidayatun Ulfa; Nashih Muhammad (Jurnal Iqtisad, 2026)
This study is motivated by a cultural phenomenon found in Traji Village, Parakan District, Temanggung Regency, namely the Suran Manten Lurah Traji tradition. In this annual tradition, held on the eve of the first day of Suro (Muharram), the village head and his or her spouse symbolically reenact a wedding ceremony. The tradition is deeply rooted in local mythological beliefs concerning supernatural powers, and the community continues to preserve it because of the belief that abandoning it would bring misfortune. This study aims to examine the implementation of the tradition and analyze it from the perspectives of 'urf (Islamic customary law) and mythology. A qualitative case study approach was employed using descriptive analysis. Data were collected through observations, interviews, and documentation involving the village head, religious leaders, community leaders, and members of the organizing committee. The findings indicate that the Suran Manten Lurah Traji tradition can be classified as 'urf 'amali (customary practice) in terms of its form, 'urf sahih (a valid custom consistent with Islamic principles) in terms of its validity, and 'urf khass (a local or specific custom) in terms of its scope. From a mythological perspective, the tradition continues to embody strong symbolic meanings and beliefs, particularly through ritual offerings (sesaji) and sacred sites that are believed to possess supernatural significance.